Stabilizing Total Mixed Ration Dry Matter to Mitigate Environmental-Relative-Humidity Effects on Lactating Cow Performance - Yi-Hsuan Chen; Yi-Ming Chen; Po-An Tu; Ching-Yi Chen; Han-Tsung Wang (Animals)
This study evaluated environmental relative humidity’s (ERH) impact on dry matter (DM) in hay and total mixed ration (TMR), exploring strategies to stabilize milk production in lactating cows by maintaining a consistent TMR DM content. We hypothesized that precise TMR DM adjustments mitigate ERH effects on milk production stability. Experiment 1 showed that grass hay exhibited greater DM variability than alfalfa hay under high ERH. Experiment 2 revealed that high daily ERH variability (>25%) caused fluctuations in hay moisture, affecting TMR DM stability. Increasing TMR DM reduced milk composition variation. In Experiment 3, precise TMR DM adjustments and heat stress levels were evaluated under different temperature–humidity indexes (THIs) in 46 cows over three 28-day periods. The results showed a significant improvement in milk yield (non-adjustment: 26.99 vs. adjustment: 27.29; SEM: 0.32; THIs: 65 to 82; p < 0.05) and a reduction in the variation in milk composition under heat stress. The differences in energy-corrected milk were lower (non-adjustment: 0.47 ± 0.06 vs. adjustment: 0.20 ± 0.09; p < 0.05). This study confirmed that monitoring hay DM and adjusting TMR DM stabilize milk production under variable ERH. Dairy producers can implement routine hay DM monitoring and TMR adjustments to enhance lactating cows’ performance.